The Neurogenic Effects of Pasak bumi (Eurycoma longifolia Jack) and Seluang Fish (Rasbora spp.) in Malnutrition-Induced Rat - Didik Dwi Sanyoto; Triawanti Triawanti; Meitria Syahadatina Noor; Dimas Ikhsan Airlangga (Folia Medica Indonesiana)
Highlights: 1. This study analyzed the effects of using locally sourced pasak bumi extract and seluang fish on the parameters of neurogenesis in malnourished rat models. 2. It promotes further exploration into modified treatments for malnutrition, emphasizing nutritional strategies that harness locally available natural resources.